Estou me guardando para quando o carnaval chegar: documentário como forma de pensar - Santos, Greiciane de Souza (2023)
We take cinema as an artifact to think the categories of work and leisure and experience and aesthetics, based on the documentary Estou me guardando para quando o carnaval chegar (2019), by Marcelo Gomes, which portrays the life of jeans workers in the Pernambuco city of Toritama. We seek to identify political, social, cultural, and aesthetic issues that cross the narratives of the characters and the narrator of the documentary, but also the very condition of filmic production of this plot. The methodological contribution is based on Cultural Studies, for understanding cinema as a cultural artifact, a means of stimulating and creating thoughts and knowledge in and for society, loaded with meanings and senses. Among the main conceptual discussions we focus on the concepts of: reality, fiction, experience, aesthetics, narrative, and the uberization of work. There are also some considerations about Pernambuco's cinema, with emphasis on Marcelo Gomes' works. The research points out that the documentary Estou me guardando para quando o carnaval chegar problematizes a new form of work organization (which consumes much of the workers' time and alters social relations and the dynamics of the city); and in counterpoint, reveals that moments of leisure are present in the daily experiences, in the moments of confidence where the workers collectively dream of enjoying the carnival - a gesture of freedom and resistance embodied by the characters. Beyond work and leisure, we can think of the documentary as forming different audiences and languages based on the concepts of experience and aesthetics.